IMPLEMENTASI STRATEGI PEMASARAN - Geransha, Rendy Viedo; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Traditional markets nowadays are being marginalized as people tend to choose modern retail stores for their shopping. In the sub-district of Blimbing in Malang city, people are becoming more consumptive. The goal of this research is to identify the implementation of STP marketing strategy, which is applied on marketing mix, to increase competitiveness. The data of this descriptive qualitative research was acquired from interviews. This study finds that the results of STP marketing strategy applied by the Blimbing branch of Alfamart on the 7Ps of marketing mix are as follows. In terms of price, the store has offered low product price, while in terms of promotion, the store has been successful in attracting customers to come. Then, in terms of product, the variants are sufficient in fulfilling the need of the customers, and in terms of place, the location of the store is already strategic and easy to find. The trading process applied by the store has been efficient, and in terms of people, the shop attendants has provided excellent services to their customers. finally, in terms of physical evidence, the store is convenient and resembles Alfamart. Those features have been effective and relevant with the components of marketing mix.